Public-Private Stewardship Achieving Value-for-Money in Public-Private Partnerships - Steinfeld, Joshua M. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
In this well-written book and valuable contribution to improving PPPs, Joshua Steinfeld provides insightful theoretical, conceptual, and practical approaches for Public-Private Stewardship practices for achieving improved VFM and PPP outcomes." - Rene Rendon, Associate Professor, Naval Postgraduate School, Monterey, CA, USA "Joshua Steinfeld has masterfully discussed and assimilated longstanding Defense and Federal acquisition tenets into and practical processes and actual examples for successful public and private sector partnerships." -Jeff Brunner, Senior Acquisition Advisor to the Chairman, U.S. Joint Chiefs of Staff (Retired), Washington, DC, USA "As governments and firms partner on large complex projects, Dr. Steinfeld provides a compelling case of the need to align public values with business interests to ensure a successful outcome. Dr. Steinfeld's tour through recent U.S. Department of Defense procurement provides an illustrative context for these increasingly common partnerships." -Trevor Brown, Dean, John Glenn College of Public Affairs, The Ohio State University, Columbus, OH, USA This book introduces public-private stewardship (PPS) as a theory and concept to achieve value-for-money (VFM) in public-private partnerships (PPPs). PPS incorporates the public stewardship tenets of fiduciary responsibility and advancing public interest factoring in private sector elements. Value propositions can be derived from shared values of transparency, accountability, efficiency, effectiveness, sustainability, innovation, and security that support decision making for inter-organizational mission, strategy, operations, and objectives. PPS practices ensue as the public-private steward utilizes competencies in procurement and contracting. Seven portraits of PPS to achieve VFM are illustrated by Department of Navy and Department of Defense examples. Joshua M. Steinfeld is Assistant Professorof Public Service, Director of the Graduate Certificate in Public Procurement & Contract Management, and Director of the Graduate Certificate in Public Sector Leadership at Old Dominion University, Norfolk, VA, USA.
1. Introduction -- 2. Leadership as Stewardship -- 3. Political Actor for Political Settlement -- 4. The Catalyst of the Public Interest -- 5. Implementation Through Communication -- 6. Transparent Engagement Across Organization -- 7. Progress from Learning and Adaptation -- 8. Stewardship Theory Over Agency Theory -- 9. Conclusion.
Keywords: Political planning; Political science; Public administration; Production management; Public Policy; Governance and Government; Public Administration; Operations Management